A Matrix Approach to the Analysis and Control of Networked Evolutionary Games with Bankruptcy Mechanism. Issue 2 (4th November 2016) - Fu, Shihua; Wang, Yuzhen; Zhao, Guodong
Abstract: This paper investigates the evolutionary dynamic and control problem for a kind of networked evolutionary games with bankruptcy mechanism by using semi‐tensor product of matrices, and presents a number of new results. First, this kind of games are expressed as logical dynamic networks and converted into their algebraic forms, based on which, the evolutionary dynamics of the given games can be discussed. Second, the control problem is considered, and a control sequence is designed to guarantee that none of players goes bankrupt as the control target requires. Finally, an illustrative example is given to show the effectiveness of our main results.